Obama’s human rights policy: déjà vu with a twist - Dietrich, John (Human rights review, 2012)
In US history, much human rights policy developed in four waves during the twentieth century. These waves were triggered by similar circumstances, but all proved short-lived as structural constraints such as limited US power over other countries’ domestic actions, competing US policy priorities, a US hesitance to join multilateral institutions, and the continued domestic political weakness of human rights advocates led to setbacks. As Barack Obama took office, his campaign comments and the past patterns led to widespread expectations that he would introduce new human rights initiatives. His policies, though, would continue to face the structural constraints and would be affected by the Bush administration’s legacy. It was predictable that many of Obama’s initiatives would be only partially implemented and only partially successful. As expected, Obama’s first years have seen mixed results, but the Obama administration has advanced US human rights policies sufficiently in half-dozen key areas to say that a fifth wave of human rights policy development is underway.